Microbiological diversity and functionality of a chronically hydrocarbon Contaminated soil post chemistry oxidation - Medina, Rocío (2015)
In situ chemical oxidation (ISCO) is increasingly used for the remediation of soil containing organic contaminants such as polycyclic aromatic hydrocarbons (PAH). However, the impact on the soil microbial community has not been thoroughly elucidated. The aim of the study was to analyze the effect of the ammonium persulfate application followed by a bioremediation process on the matrix, microbial community and the PAH removal of the soil. Chronically contaminated soil (S) was collected from a petrochemical area (214 ppm PAH). Ammonium persulfate (PS) was sprayed as aqueous solution on contaminated soil by three additions (1% wt/wt) every two days and incubated at 30°C ( SOx). S and SOxwere further incubated at 25°C, 25% moisture content, mixed and monitored for 28 days. These microcosms were named SB and SOxB respectively. The PAH concentrations were determined by GC-FID. No PAH elimination was detected in SB. A significant elimination (35%) was observed in SOx while no additional decrease was detected SOxB. Alkaline extraction was performed to obtain an aqueous solution of natural organic matter of the soil. The Total Organic Carbon contents (TOC, TOC-5000 Shimadzu) and the Fluorescence Excitation Emission Matrixes (FEEM, Perkin-Elmer LS-50B) were determined for Sand SOx. FEEM of Spresents two zones of emission. The zone on lexc ~ 320 nm and lem ~ 440 nm could be assigned to the presence of PAH. These emissions were absent in SOx in line with the PAH elimination, and a significant increment on TOC values was also detected. A significant decrease in the microbial counts was observed in SOx. The subsequent bioremediation only increased the heterotrophic bacterial population which suggested that the available organic carbon allowed the growth of this population. To evaluate the microbial activity, four enzymes lipase, aril sulphatase, urease and protease were analyzed. All of them were slightly expressed in S microcosms and only lipase activity was significantly increased in SOx. Seed germination test using Lactuca Sativa on water extracts was performed to evaluate the soil toxicity. The toxicity detected in S was exacerbated in SOx and it was not reversed in SOxB. The dynamics of the bacterial community structure, analyzed by 16S rRNA PCR DGGE, evidenced a great change due to the oxidation. The clustering among the S and SOxB profile bands suggested the tendency of SOxB to recover the original structure. The pyrosequence analysis showed that members of actinobacteria, bacilli and acidimicrobiia classes were the predominant populations in SOx. Members of the actinobacteria became the dominant population in SOxB. This group was considered as k-strategist microorganisms and a major component in the later stages of successions in bioremediated soils. The initial PAH elimination provoked by PS was not followed by an additional elimination under bioremediation condition. However, a microbial succession of generalist populations was observed